Aportes de la Comunidad Andina (CAN) en la relación medio ambiente y municipios (2020)
The authorities (mayors and councilors) of each municipality must promote in their development plans the adequate protection and conservation of the environment, taking into account that this is precisely what the Andean Community (can), an organization of which Colombia is a member. This is why this article seeks to highlight the contributions of the can to the relationship between the environment and municipalities. In this sense, the research problem to be solved is whether the can has contributed to improving the legal relationship between the environment and municipalities. All of the above within the framework of a qualitative methodology and from the scenario of the dogmatic method.